A unified multi-soft-body dynamic model for underwater soft robots. (May 2018) - Renda, Federico; Giorgio-Serchi, Francesco; Boyer, Frederic; Laschi, Cecilia; Dias, Jorge; Seneviratne, Lakmal
A unified formulation that accounts for the dynamics of a general class of aquatic multi-body, soft-structured robots is presented. The formulation is based on a Cosserat formalism where the description of the ensemble of geometrical entities, such as shells and beams, gives rise to a multi-soft-body system capable of simulating both manipulation and locomotion. Conceived as an advanced tool for a priori hardware development, n-degree-of-freedom dynamics analysis and control design of underwater, soft, multi-body, vehicles, the model is validated against aquatic locomotion experiments of an octopus-inspired soft unmanned underwater robot. Upon validation, the general applicability of the model is demonstrated by predicting the self-propulsion dynamics of a diverse range of new viable combinations of multi-soft-body aquatic system.